DsbA-L Ameliorates Renal Injury Through the AMPK/NLRP3 Inflammasome Signaling Pathway in Diabetic Nephropathy - Yang, Ming; Luo, Shilu; Jiang, Na; Wang, Xi; Han, Yachun; Zhao, Hao; Xiong, Xiaofen; Liu, Yan; Zhao, Chanyue; Zhu, Xuejing; Sun, Lin (Frontiers in Physiology, 2021)
NLRP3-mediated inflammation is closely related to the pathologic progression of diabetic nephropathy (DN). DsbA-L, as an antioxidant enzyme, plays a protective role in a variety of diseases through inhibiting ER stress, metabolic regulation and so on. However, its relationship to inflammation, especially NLRP3 inflammasome, has not been studied. In this study, we noted that the activation of NLRP3 inflammasome and aggravating fibrosis were observed in the kidney of diabetic DsbA-L knockout mice, which accompanied by the decreased of AMPK phosphorylation. Moreover, correlation analysis showed that the phosphorylation of AMPK was negatively correlated with NLRP3 expression and tubular damage. In addition, decreased AMPK phosphorylation and activation of NLRP3 induced by high glucose in HK-2 cells can be alleviated by overexpression of DsbA-L. Interestingly, the protective effect of DsbA-L was eliminated once treated with compound C, an accepted AMPK inhibitor. Our findings suggest that DsbA-L inhibits NLRP3 inflammasome activation by promoting phosphorylation of AMPK.